(untitled) (Colección, 2017)
The aim of this paper is to review the bibliography both directly and indirectly related to the Fuerzas Armadas Revolucionarias (FAR), political-military organization of Marxist-Guevarist extraction which operated at the early 70‘s in Argentina. To that effect, we review what we take to be the most significant aspects of the works that attempt to study the context where the armed revolutionary organizations emerged, their trajectory and also those specifically oriented to the FAR, so as to achieve a revision as encompassing as possible. We also search for bibliography that allows to think the political trajectory of the FAR in relation to the evolution of Argentine history and revolutionary leftist partisanship in the peculiar context of the country since 1955. One of the latent intuitions of the paper is that the FAR express, in their development, in an exemplary manner phenomena that had a particular relevance at the time, such as the radicalization of leftist partisanship and the concomitant "peronization" of a significant part of those sectors that came mainly from the middle classes and the younger segments of the population